Prevalence of Nerve Injuries in Supracondylar Fracture of Humerus in a Tertiary Care Hospital - Panta, Sunil; Thapa, Sushil; Hamal, Bhadra; Bhandari, Pratap Babu; Paudel, Krishna Prasad; Thapa, Shrawan Kumar (Journal of Nepal Health Research Council, 2021)
Background: Supracondylar fracture is a common childhood injury. These fractures are often associated with neural and vascular injuries. There is discrepancy in literature about the most common nerve injured in such fractures. This study aims to study the nerve injury patterns in supracondylar fractures of humerus in Nepalese children.Methods: This descriptive cross sectional study was conducted in 152 children (aged 2 to 14 years) with supracondylar fractures of humerus attending in Bharatpur Hospital during the period of one year. All eligible patients were assessed clinically and radiologically. Neurological assessment was done for nerve injury.Results: Out of 152 children, 18(11.8%) had nerve injuries. The mean age was 7.41±2.91 years. Boys were more injured (68.4%) than girls (31.6%). It was more common on non-dominant side (57.9%). Out of 18 nerve injuries, most commonly injured nerve was median nerve 10(55.5%) followed by radial nerve 7(38.9%). Median nerve injury was common in posterolateral displacement and radial nerve injury was common in posteromedial displacement type of fracture.  Conclusions: Displaced supracondylar fractures have relatively higher prevalence of nerve injuries. Most commonly involved nerve is median nerve followed by radial nerve. So, every displaced fracture should be routinely screened for nerve injuries.Keywords: Humeral fractures; median nerve; peripheral nerve injuries; prevalence; radial nerve